Design and synthesis of RNA miniduplexes via a synthetic linker approach. 2. Generation of covalently closed, double-stranded cyclic HIV-1 TAR RNA analogs with high Tat-binding affinity. - X Ma, M Y (1993)
We recently developed an approach which allows rapid generation of short, double-stranded oligonucleotides whereby one end of the duplex was joined and stabilized by a synthetic linker of specific design (miniduplexes)(6). Model miniduplexes based on the HIV-1 TAR RNA hairpin were shown to be thermodynamically stable and good substrates for binding by the HIV-1 Tat protein which normally bind to natural TAR (6). In this study, we have extended our studies to the design, synthesis and analysis of the binding properties of covalently closed, double-stranded, cyclic RNA miniduplexes. A strategy using automated chemical synthesis and T4 RNA ligase-catalyzed cyclization was employed to generate cyclic oligoribonucleotides. When both ends of a shortened, wild-type TAR RNA stem (9 bp) were covalently linked through either nucleotidic loops (4-6 nt) or synthetic linkers (derivatized from hexaethylene glycol), the resulting cyclic TAR RNA analogs were good substrates for binding by both Tat-derived peptide or full-length Tat protein. Interestingly, the cyclic TAR analogs failed to show any binding if the synthetic linker was reduced in length (e.g. derivatized from triethylene glycol), although such linkers are acceptable in the hairpin-shaped miniduplexes series (6). This implies that RNA conformational changes are required for Tat binding and that these changes are restricted in certain cyclic variants. Our findings suggest that covalently-closed nucleic acid miniduplexes may be useful both to study nucleic acid-protein interactions as well as to provide a basis for therapeutic intervention as transcription decoys.